STRATEGI POLITICAL MARKETING KANDIDAT DALAM PILKADES - Arif, Muhammad (LPPM Abdurrab Pekanbaru, 2017)
This study aims to determine the political strategy of marketing is done by M. Fauzi in winning the Village Head Election (Pilkades) Sungai Ara District of Indragiri HilirKempas 2015. This research is a descriptive study using a qualitative approach. The data used are primary data and secondary data. The primary data of the research results informant interviews and observations conducted by researchers. While secondary data in the form of reports and official documents. The results show that the candidate can apply political marketing strategy well. political marketing by M. Fauzi more progressive compared to other candidates. M. Fauzi use of political marketing approach Oriented Party Products (POP). Focuses its products such as past records, a character or personality that is either done in the past long before Pilkades held. Such products are promoted through marketing strategies pass and push political marketing Pass political marketing is done by means of direct visits to people's homes and participate in associations or informal organizations. While the political Push marketing is done through community leaders, community leaders and associations taklim assemblies that became a campaign team.